Strong Upper‐Plate Heterogeneity at the Hikurangi Subduction Margin (North Island, New Zealand) Imaged by Adjoint Tomography. Issue 1 (17th January 2022) - Chow, Bryant; Kaneko, Yoshihiro; Tape, Carl; Modrak, Ryan; Mortimer, Nick; Bannister, Stephen; Townend, John
Abstract: We use earthquake‐based adjoint tomography to invert for three‐dimensional structure of the North Island, New Zealand, and the adjacent Hikurangi subduction zone. The study area, having a shallow depth to the plate interface below the North Island, offers a rare opportunity for imaging material properties at an active subduction zone using land‐based measurements. Starting from an initial model derived using ray tomography, we perform iterative model updates using spectral element and adjoint simulations to fit waveforms with periods ranging from 4–30 s. We perform 28 model updates using an L‐BFGS optimization algorithm, improving data fit and introducing P ‐ and S ‐wave velocity changes of up to ±30%. Resolution analysis using point spread functions show that our measurements are most sensitive to heterogeneities in the upper 30 km. The most striking velocity changes coincide with areas related to the active Hikurangi subduction zone. Lateral velocity structures in the upper 5 km correlate well with New Zealand geology. The inversion reveals increased along‐strike heterogeneity on the margin. In Cook Strait we observe a low‐velocity zone interpreted as deep sedimentary basins. In the central North Island, low‐velocity anomalies are linked to surface geology, and we relate velocity structures at depth to crustal magmatic activity below the Taupō Volcanic Zone. Our velocity model provides more accurate synthetic seismograms with respect to the initial model, better constrains small ( < $< $ 50 km), shallow ( < $< $ 15 km) and near‐offshore velocity structures, and improves our understanding of volcanic and tectonic structures related to the active Hikurangi subduction zone. Plain Language Summary: We perform seismic imaging of the Earth's crust below the North Island of New Zealand, which sits above an active plate boundary known as the Hikurangi subduction zone. By comparing computer simulations of earthquake ground motion with recordings of ground motion, our imaging method iteratively improves models of Earth's subsurface structure. Our data set consists of earthquake waveforms from 1, 800 unique source–receiver pairs. We incrementally update the seismic velocities of the initial model 28 times, resulting in velocity changes of up to ±30%. Variations in the subsurface structure are most strongly resolved in the upper 30 km. Seismic velocity structures in the upper 5 km correspond well with known surface geology. The strongest velocity changes correspond to regions related to the Hikurangi subduction zone, such as a deep sedimentary basin in Cook Strait, and anomalous velocity structures related to the Taupō Volcanic Zone. The newly derived velocity model improves predictions of earthquake ground motion and improves our understanding of volcanic and tectonic structures associated with the active Hikurangi subduction zone. Key Points: We develop a high‐resolution (4–30 s) 3D velocity model of the North Island of New Zealand with 28 adjoint tomography iterations Distinct P ‐ and S ‐wave velocity changes of up to ±30% are made to the existing model in the upper 30 km The tomographic results provide improved images of tectonic and magmatic structures throughout the Hikurangi subduction margin